Perceptions of the Nazi Mind: Psychological Theories, 1940s-Present - Pieper, Taylor (My University, 2013)
Since the Holocaust, psychologists have attempted to explain the mindset of the Nazi men who performed such atrocities. To most, the horrors of the Holocaust are unfathomable and thus trying to understand the psychology of the men behind it is nearly impossible. Throughout the years, however, psychologists have attempted to do just that. There have been a plethora of theories as to what the mindset of these genocidal murders was. These theories have evolved and changed overtime, however, and thus the American public perception of Nazis has changed right along with them. This paper will explain the changing theories throughout the years as well as the American perceptions of Nazis that echo them.
Keywords: Nazis--Attitudes; Nazis--Psychology; Nazis--Public opinion